SIMULAÇÃO VIA ELEMENTOS FINITOS DA ETAPA DE RESFRIAMENTO DA MOLDAGEM ROTACIONAL - Canova, Cláudia Francine Machado (2004)
The purpose of the present work was to simulate the cooling phase of the rotational molding in order to evaluate the influence of some variables in the cooling time, that is the longest one in the process. ANSYSTM software was used to perform the simulation using the finite element method, thus it will be possible to work with complex geometries in future works. However, in the present simulation a spherical mold was used. The effect of the crystallization process of polymer during the cooling phase was evaluated by the incorporation of the heat of crystallization in the curve of enthalpy. Using this procedure it was possible to observe the effect of the crystallization process on the temperature profile as a function of time for the polymeric part. It was possible to compare this profile with the correspondent theoretical curve for a similar amorphous polymer. It was evaluated also the effect of different values of convection heat transfer coefficients for the external air and the effect of using a polymer with a higher thermal conductivity, associated to the use of fillers as the aluminum. The validation of the simulated results of the cooling phase of rotational molding was done by comparison with experimental and simulated results from literature, being obtained good agreement. In present work it was performed also a validation of the ANSYSTM simulation of solidification process of polymers involving crystallization by comparison with data from quenched slabs experiments. In this case, low density polyethylene samples and low density polyethylene with aluminum, from recycled Tetra Pak packages, were used in disc shapes and submitted to quenching, being recorded the temperature profile as a function of time in different cooling rates. The simulation in the software ANSYSTM allowed a good agreement between experimental and simulated curves. It was vii observed that the convection heat transfer coefficient for the external air is the main variable that control the process and that the thermal conductivity of polymer does not play an important role in the process. It was observed also that the heat released in the crystallization process presents a significant role and that it is important to include this phenomena in the simulation.